(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The article is of a review nature and considers issues related to the causes formation of odontogenic phlegmons from the point of view of scientific views. The opinions of different authors on the subject under study. Research recent years indicate that the leading direction in the study of odontogenic phlegmon in purulent maxillofacial surgery make up work aimed at studying the state of the body’s immune reactivity with clarification of the state of non-specific and cellular immunity as the dominant factor in the development and course of odontogenic inflammatory diseases of the maxillofacial area and neck